Multiple lipid biomarkers record organic matter sources and paleoenvironmental changes in the East China Sea coast over the past 160 years. (January 2021) - Chen, Lilei; Li, Feng; Liu, Jian; He, Xingliang
The use of lipid biomarkers as paleoenvironmental proxies relies on an accurate assessment of their organic matter (OM) sources. In this study, we analyzed multiple lipids in core sediments recovered from the Zhejiang–Fujian coastal mud area to provide a 160-year record of OM input to the East China Sea (ECS) coastal sediments and to reconstruct paleoenvironmental conditions over this interval. The molecular composition of the samples was characterized by a mixture of natural lipids, particularly those derived from terrestrial vascular plants, marine/riverine plankton and macrophytes, and bacteria. The sources of some lipid components were ambiguous/mixed as they were potentially derived from multiple precursor organisms and because of limitations associated with modern survey techniques. There is evidence that early diagenesis caused the preferential degradation of labile aquatic lipids and that the degradation of terrestrial lipids was more severe when subjected to complex horizontal–vertical transportation processes associated with deposition, resuspension, and redeposition. These processes may have led to an enhanced terrestrial OM signal in the normal ( n )-alkane and n -alkanol records, which is at odds with, for example, those of the n -fatty acids, hopanoids, steranes, and sterols, which suggest a dominant marine OM source. Furthermore, we conclude that the occurrence of multiple sources, selective diagenesis, and test error has led to the distortion of redox and maturity indicators based on evidence from pristane-to-phytane (Pr/Ph) ratios and sterane/hopane indices in century scale. Overall, the phytol record suggests an increase in productivity after the early 20th century. Correspondingly, the diatom lipid biomarker records (based on C25 highly branched isoprenoid alkenes and C18:1ω9 fatty acids) reveal a fluctuating but overall increasing diatom productivity after the early 20th century, which coincides with a decreased proportion of the contribution from diatoms relative to that of total phytoplankton. This is believed to correspond to natural environmental changes, as well as anthropogenic impact.